Collective Worldview of Indigenous Communities in The Oral Literature of Dayak Keninjal Pameo - Devi Anggraini; Ikhza Mahendra Putra; Sesilia Seli (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Oral literature in Indigenous communities’ functions as a symbolic medium that records and transmits a collective worldview. One of its forms is pameo, a concise expression that affirms values and norms within social life. Among the Dayak Keninjal community, pameo serves not only as motivational slogans but also as representations of moral principles and perspectives on social and environmental relations. This study aims to uncover the collective worldview embedded in Dayak Keninjal pameo. Unlike previous proverb studies, this research positions pameo as a representation of a collective worldview through a cultural semantic approach. The study employed a descriptive qualitative method, with data consisting of ten pameo collected through interviews and field documentation in January 2026. The analysis was conducted through the identification of lexical meanings and cultural semantic interpretation. The findings indicate that Dayak Keninjal pameo reflect five interconnected life orientations: togetherness, resilience, creativity, steadfast responsibility, and brotherhood and deliberation, with action as the core of meaningful life. These findings contribute to the theoretical and empirical enrichment of oral literature and cultural semantics studies by reinforcing the concept of worldview grounded in local wisdom.